Population, ethnicity, and nation-building - Goldscheider, Calvin (Brown University studies in population and development, 1995)
This volume focuses on the linkages between ethnicity and population processes in the context of nation-building. Using historical and contemporary illustrations in a variety of countries, parts of this complex puzzle are scrutinized through the prisms of sociology, history, political science, anthropology, and demography. Themes of ethnic group formation and transformation, persistence and assimilation, demographic transitions and convergences, and the processes of political mobilization and economic development are described and compared. Case studies from Southeast Asia, China, Africa, Brazil, Israel, the former Soviet Union, Canada, Europe, and the United States are presented by leading scholars. The examples illustrate the diversity of contexts that connect population, ethnicity, and nation-building, raising new questions and comparative problems.